Continuous real-time analysis of the isotopic composition of precipitation during tropical rain events : insights into tropical convection - He, Shaoneng (2018)
To investigate stable isotopic variability of precipitation in Singapore, we continuouslyanalysed theδ‐value of individual rain events from November 2014 to August 2017using an online system composed of a diffusion sampler coupled to Cavity Ring‐DownSpectrometer. Over this period, the average value (δ18OAvg), the lowest value(δ18OLow), and the initial value (δ18OInit) varied significantly, ranging from−0.45 to−15.54‰,−0.9 to−17.65‰, and 0 to−13.13‰, respectively. All 3 values share sim-ilar variability, and events with lowδ18OLowandδ18OAvgvalues have lowδ18OInitvalue.